Electrochemical treatment of highly concentrated wastewater: A review of experimental and modeling approaches from lab- to full-scale. Issue 2 (17th January 2022) - Garcia-Rodriguez, Orlando; Mousset, Emmanuel; Olvera-Vargas, Hugo; Lefebvre, Olivier
Abstract: This review proposes an insight into the prospects of electrochemistry for the treatment of highly concentrated effluents in three sections. The first section of this review presents an overview of electrochemical water treatment strategies adapted to these very specific waste streams, including the influence of operating conditions, electrode materials and processes (with special emphasis on anodic oxidation, electro-Fenton and electrocoagulation). The second part provides the engineering parameters to ensure successful upscaling of electrochemical processes in terms of modeling mass transport, charge transfer and hydrodynamics, reactor designs and energy requirements. This section also addresses process combinations, where electrochemistry could complement traditional methods of treatment, in order to improve the overall efficiency of the integrated system. Finally, the last section focuses on the nature, characteristics and challenges inherent to highly concentrated wastewater, divided into five categories: industrial wastewater (e.g., pharmaceutical, electronics, chemical, food-processing), hypersaline effluents (e.g., reverse osmosis concentrates), solutions contaminated with a mixture of organic and inorganic contaminants (e.g., leachate, mining), highly viscous solution (or non-Newtonian liquid) (e.g., sludge) and solutions of high chemical oxygen demand load but with low pollutant content (e.g., from soil washing). Graphical abstract: UF0001